THE OXIDATION STATE OF IRON IN SILICIC MELT AT 500 MPA WATER PRESSURE - Wilke M.; Behrens H.; Burkhard D.J.M.; Rossano S. (My University, 2002)
The dependence of the ferric-ferrous ratio in silicate melts on oxygen fugacity was studied in the system SiO2(Qz)-NaAlSi3O8(Ab)-CaAl2Si2O8(An)-H2O using Mossbauer spectroscopy. Experiments were performed under water-saturated conditions at 500 MPa, and at temperatures of 850 and 950 °C, covering a range typical for magmatic processes. The oxygen fugacity was varied in the fO2 range from Cu-Cu2O buffer to slightly more reducing conditions than the wustite-magnetite buffer. The iron redox ratio was determined by analyzing the Mossbauer parameter distribution that was modeled based on experimental spectra collected at room temperature on the quenched samples. The obtained iron redox ratios show a linear dependence on oxygen fugacity on a logarithmic scale for both temperatures. The iron redox ratio (Fe3+/Fe2+) decreases with temperature for a given oxygen fugacity. The spectroscopic data at 850 °C are in good agreement with Fe3+/Fe2+ ratios derived from element partitioning but show considerable deviations from iron redox ratios predicted by the empirical equation given by Kress and Carmichael [Contrib. Mineral. Petrol. 108 (1991) 82]. This indicates that an extrapolation of this equation to such low temperatures may have large errors. A sample quenched slowly through the temperature range near and below Tg shows considerable differences in the obtained Mossbauer spectra compared to more rapidly cooled samples, indicating ordering of the iron environment at least in the mesoscopic range. The oxidation state, however, does not differ when compared to the more rapidly quenched melts.
Keywords: IRON OXIDATION STATE; SILICATE MELT; OXYGEN FUGACITY; MOSSBAUER SPECTROSCOPY